Implementasi Perencanaan Produksi dan Kapasitas Mesin Guna Meningkatkan Efisiensi Produksi: Systematic Literature Review - Nia Mintari; Masduki Asbari; Nidia Astuti (Yayasan Aya Sophia Indonesia, 2024)
The process of planning production and machine capacity is the implementation of a production process that is complementary and sustainable. The problem with the production process starts with a scheduling process that is less than optimal. The condition of the machine is often ignored because we are too focused on carrying out the production process. This research aims to examine journals regarding production planning in a company. Starting with looking for sources of scientific work in international journals and national journals. Retention in journal searches starts from 2004 to 2024. Researchers obtained 6 scientific articles on production planning and machine capacity which have an impact on increasing efficiency in production. Good planning can also help company management achieve the company's expected targets.